Foreign Aid’s Effect on Political Risks for Foreign Direct Investment: A Literature Review - V. I. Bartenev (Vestnik MGIMO-Universiteta)
The last decade has seen an increasing focus on the involvement of the private sector in international sustainable development, particularly in high-risk jurisdictions. This involvement encompasses a broad spectrum, incorporating innovative private sector instruments—now acknowledged as ODA-eligible by the OECD—as well as traditional tools of external official support to developing countries, which remain the primary contributors to ODA flows. This literature review aims to consolidate the academic exploration of the enduring classic foreign aid tools' impact on the political risks associated with foreign direct investment (FDI), and identifies prevalent limitations while suggesting approaches to overcome these challenges.The first section delineates the central theme and rationale behind the literature selection process, utilizing the Google Scholar database to contextualize the research within a comprehensive framework. The subsequent section categorizes and compares the most relevant studies based on formal criteria and methodological parameters. Sections three and four critically assess the scholarly contributions in conceptualizing the mitigating influence of foreign aid in general, focusing on its impact on specific political risks such as expropriation, terrorism, and corruption. The concluding section delves into studies that explore foreign aid and foreign direct investment flows from China, the largest non-Western donor.A bibliometric analysis reveals a noteworthy disparity between research attention and policymaking focus on the subject matter. Notably, the selected papers fail to comprehensively cover the full spectrum of primary extra-legal and legal-governmental political risks for transnational businesses. Scholars' assessments of foreign aid's mitigating effect often lack differentiation between grants and loans or between flows directed to different sectors, as well as the distinction between aid routed through public institutions and bypassing them. Notably absent is a comprehensive analysis encompassing the complete range of 'established' Western and emerging non-Western aid providers, or an exploration of aid flows from non-OECD countries other than China. Most research focuses on Africa and fails to differentiate between recipients based on fragility, income levels, or other relevant categorizations. Moreover, the researchers have yet to delve into data post the COVID-19 outbreak, a critical period that significantly altered perceptions of political risk, foreign aid, and FDI flows. The literature review illuminates a research gap awaiting substantial exploration.